The ’4 As’ of Rural Marketing Mix - Pallavi (Indian Journal of Marketing, 2011)
The rural markets are green pastures for companies today, as they are growing faster as compared to the urban markets. With their huge size and demand base, they offer great opportunities to the marketers. More than three-fourths of the country’s consumers reside in rural areas and more than half of the national income is generated by them. Stagnant urban demand and relative rural prosperity are attracting companies to the rural markets for selling their products and services. Apart from the traditional agricultural income, government spending and infrastructure, projects have meant a cash flow in these markets. Companies are connecting to this base afresh and are getting their acts together to cater to this market effectively and efficiently. The overall marketing mix framework for rural markets necessarily focuses around delivering the right product, using value for money pricing, using effective means of promotion, selecting the most appropriate method of distribution and building long-term relationships with the customers. Consequently, in case of rural marketing, the marketing mix has changed from the traditional ’4 Ps’ to the new ’4 As’, i.e., affordability, awareness, availability and acceptability. In fact, rural markets have unlocked new fronts for the modern marketers.